Beyond the Income Effect : Impacts of Conditional Cash Transfer Programs on Private Investments in Human Capital - Cruz, Marcio; Ziegelhofer, Zacharias (World Bank, Washington, DC, 2014)
In the past decade, conditional cash transfer (CCT) programs have become an important component of social policy in developing countries. While the impacts of these programs have been well researched with respect to their effectiveness to achieve intended outcomes, less is known about their impact on private expenditure decisions. This aspect has great policy relevance since changes in private household expenditures can either support or counteract the aim of the programs. This essay investigates the impact of a CCT program on private household expenditure decisions in nutrition, health and education which are seen as principal contributors to child human capital. First, household expenditure behavior under a CCT program is discussed based on Heckman's model on the technology of skill formation as a conceptual framework. The paper shows how intra-household preferences and perceptions on the substitutability or complementarity of investments can impact household resource allocation decisions. Subsequently, the theoretical implications are tested in the context of the Brazilian CCT program Bolsa Família, using the Brazilian household expenditure survey. Evidence is found that households increase their private expenditure in food and education disproportionally to the amount of cash transfer, that is, more than would be expected when considering the Engel curves of the expenditures under question.